Numerical simulations of the effects of tarpaulin billowing on phosphine movement in bulk-stored grain - Elsayed, Sherif Mohamed Gomaa (Kansas State University, 2023)
Bunker storage is an inexpensive, and thus popular, method for medium- and long-term storage of wheat. To control insect infestations in bunker storages, phosphine (PH3) fumigant is commonly used, especially in Australia, due to its relatively low price and the near absence of residual chemicals on the grain. Understanding the behavior of phosphine gas inside bunkers is crucial to maintaining a lethal dosage and protecting stored grain from subsequent insect damage. Gases in bunkers experience pressure drop and a change in velocity due to the presence of wheat. In Computational Fluid Dynamics (CFD) simulations, wheat kernels are not modeled explicitly in the geometry, rather their effect in terms of pressure loss is considered in the governing equations. This study reviews the wheat resistance to gas flow and its characteristics. Physical properties of the isotropic and anisotropic resistances were discussed. Proper coefficients that reasonably describe the presence of wheat in CFD models were chosen. This is important to understand the fumigant distribution in a grain storage facility. To test the implementation of these coefficients in CFD simulations, a CFD model was built and the results agreed well with the published empirical correlations. Detailed explanations on the governing equations used in all the simulations were also discussed. A new technique in obtaining the resistance coefficients without the need for any experimental work was proposed and verified against published experimental data. Phosphine is available either in gas form or is produced from a solid material, as pellets or tablets of aluminum or magnesium phosphide, that react with moisture in the air. The solid form is the most commonly used; however, limited information is available on the rate of phosphine gas generated from the solid material. In this study, a mathematical equation was formulated, based on previous studies in the literature, to describe the gas generation rate. This equation was incorporated into a CFD model. The computational model developed here allows prediction of the phosphine concentration within a fumigated grain bulk. The PH3 sorption was included in the model. The effect of temperature on the sorption rate was investigated based on published data, and the rate change due to temperature was characterized. To validate the model, the gas generated by a single pellet was measured in laboratory experiments in a 0.208m3 sealed barrel. The measurements confirmed the CFD results with an error of 0.3%, 0.9%, and 7.2% for three different configurations. The deviations seen between the experimental replicates increased the error and showed the need for further investigation of the effects of temperature, grain age and history, leakage, and other factors. For fumigation to be effective, a lethal concentration of PH3 for a minimum time period at an optimal temperature throughout the bunker must be ensured. Because bunkers are exposed to ambient conditions, temperature gradients are created throughout the bunker, resulting in natural convection currents that move PH3 from areas around the fumigation points to the entire bunker. CFD simulations were used to investigate the effect of natural convection on fumigation in bunkers. The model was validated against published benchmarks and a field experiment with a full-scale bin with sorption and leakage. The effects of PH3 release point locations, bunker shape, bunker orientation, leakage, sorption, ambient temperature fluctuation, and PH3 motion in three dimensions were studied. Results showed that diffusion and natural convection solely are insufficient in spreading out PH3 within bunkers. In addition to diffusion and convection currents, the internal flows driven by the movements of the covering tarpaulin due to the external flow over the bunker, distribute the PH3 gas. This study also aims to describe the effect of tarpaulin movement on the PH3 behavior inside bunkers. The motion mechanism of the tarpaulin was investigated using Fluid-Structure Interaction (FSI) simulations under different wind conditions. The FSI study was validated against published benchmarks. The dominant motion of the tarpaulin was then simplified and built in a CFD model with non-linear moving boundaries to study its effect on the PH3 distribution. Results were concluded using a Deep Neural Network (DNN) model. Results showed that tarpaulin motion, as a free source, can immensely improve the fumigation effectiveness, if controlled properly. A small change in the motion parameters resulted in a very different PH3 distribution and a different enhancement rate. The challenges on unifying a certain motion with certain parameters on the currently built bunkers such as the smoothness of the grain surface, the looseness and tightness of the tarpaulin with the side walls of the bunker, etc. were discussed. Highlights on the importance of building a more controlled and semi-sealed tarpaulin mechanism were pointed out.
Keywords: CFD; FSI; Phosphine; Wheat; Bunkers